Ø§Ù„Ø¥Ø¹Ø¬Ø§Ù… ÙˆØ§Ù„Ø¯Ù„Ø§Ù„Ø© Ø§Ù„Ù…Ø¬Ø§Ø²ÙŠØ©: Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„ØØ¯ÙŠØ«Ø© - Safi, Khadidja Mohammed (Hijai - Journal on Arabic Language and Literature, 2023)
The Arabic dictionary had - and still is - a great role in preserving the Arabic language in terms and methods. The dictionary was a means of understanding what was hidden from the verses of the Noble Qurâ€™an, as well as what was formed from the ancient texts, poetry and prose, for this, the dictionary contributes directly to memorizing and to protect the Qurâ€™an and the words of the Arabs by documenting vocabulary. It is the failure of these dictionaries to capture all the meanings of a single word, to show the enormity of this problem when non-Arabs rely on these easy dictionaries in order to learn the Arabic language. The significance is the result of the interaction of the individual with the context, and herein lies the importance of this research; It has been noted that most modern Arabic dictionaries lack reference to the figurative (Al-majaz)significance of the word, and as it is known that the lexical meaning alone does not express the meaning of the word, but the contextual significance must be taken into account sometimes to determine the meaning of the speech. To reduce the use of Arabic words in reality, as the lexicon is intended to be the best way for the Â Ajami to master Arabic as a second language, without marginalizing the suggestive connotations that can be considered a unique feature of the Arabic language compared to other languages due to the diversity of linguistic styles in it., Therefore, the method of this research will be descriptive and comparative to count the semantic deficiencies in these dictionaries; electronic ones in particular, in order to develop the Arabic dictionary in line with the era of globalization, and thus the Arabic language precedes other languages in spread by facilitating its learning.